2017
DOI: 10.1002/hed.24786
|View full text |Cite
|
Sign up to set email alerts
|

Transoral robotic retropharyngeal node dissection in oropharyngeal squamous cell carcinoma: Patterns of metastasis and functional outcomes

Abstract: RPLND is technically feasible by a purely transoral robotic approach. Its performance is not associated with worse swallowing outcomes or rates of complication. In select patients, RPLND may provide valuable staging information and guide the selection of adjuvant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 17 publications
1
25
0
1
Order By: Relevance
“…TORS is a safe and mini‐invasive approach to a critical anatomic area such as the retropharynx. Magnification, 3D vision, and articulated arms provided by the robotic arms allow for a comfortable dissection in a narrow space even in close proximity to critical structures such as the parapharyngeal internal carotid artery and sympathetic chain …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TORS is a safe and mini‐invasive approach to a critical anatomic area such as the retropharynx. Magnification, 3D vision, and articulated arms provided by the robotic arms allow for a comfortable dissection in a narrow space even in close proximity to critical structures such as the parapharyngeal internal carotid artery and sympathetic chain …”
Section: Discussionmentioning
confidence: 99%
“…In this particular case, as the patient has already had a total laryngectomy, both airway protection and surgical exposure did not represent an issue. Generally speaking, other experiences in literature report no necessity of temporary tracheotomy when dealing with retropharyngeal node dissection through a TORS approach . The daVinci Si system was equipped with a 0°degree camera, a 5 mm Maryland forceps, and a 5 mm monopolar cautery that were placed in the center, left, and right side of the surgical field, respectively.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Historically, RPLN metastases have been associated with decreased overall survival. Reports in the literature have shown metastatic rates ranging from 13% to 36% and more commonly with tonsil primaries.…”
Section: Discussionmentioning
confidence: 99%
“…Reports in the literature have shown metastatic rates ranging from 13% to 36% and more commonly with tonsil primaries. 31 Lymphoscintigraphy would be a method of determining which patients with OPSCC have retropharyngeal drainage patterns thus either requiring a RPLN dissection or irradiation for proper management of this lymphatic basin. [31][32][33] A study by Troob et al reported their incidence of metastatic RPLNs in T1-T3 OPSCC patients to be 20% (n = 6).…”
Section: Discussionmentioning
confidence: 99%